Routine Activities and Deviant Behaviors: American, Dutch, Hungarian, and Swiss Youth - Vazsonyi, Alexander Thomas (Journal of quantitative criminology, 2002)
The current investigation examined cross-national similarities and differences in routine activities, measures of deviance, and their relationship in representative samples of 7,000 adolescents aged 1519 years (mean age: 17.5 years) from Hungary, the Netherlands, Switzerland, and the United States. For the majority of youth, most of their time was spent in solitary activities, followed by peer activities, community/sports activities, and family activities; Hungarian youth reported spending a much greater amount of time with the family than adolescents from other countries, while Dutch youth spent far more time in solitary activities than their peers. Rates of total deviance were remarkably similar for American, Dutch, and Swiss youth; Hungarian youth reported substantially lower rates than all other adolescents. Finally, findings indicated that routine activities accounted for 18% for males and 16% for females of the variance explained in total deviance. Furthermore, with the exceptions of alcohol and drug use, country had very little or no explanatory power in deviance. The current study suggests that the utility and the explanatory power of the routine activities framework replicates across national boundaries.